Seismic Performance of an RC Building Using Pushover Analysis : (Case Study: Three-Storey Flat House Building in Padang City) - Windy Wulandari; Syafri Wardi (Universitas Medan Area, 2023)
Indonesia is located in a high seismic risk area, and past earthquakes have caused many death tolls due to building collapses. Therefore, evaluation of the seismic performance of existing buildings is critical to minimize the risk due to earthquake damage. This study is aimed to evaluate the seismic performance of a three-story flat house building in Padang city, Indonesia. The building was designed based on the older seismic design code SNI 1726:2012. Based on a previous study, if the structure is analyzed using the latest seismic design code SNI 1726:2019, the dynamic base shear force increases by about 20%. Therefore, further analysis needs to be conducted using pushover analysis. The pushover analysis results are capacity curve, displacement or drift, performance point, performance level, and plastic hinge mechanism of the building. The analysis results show that the performance level of the building after the pushover analysis in the x and y directions is immediate occupancy with the plastic hinged formed firstly at the end of the beam. This performance level means that the damage due to an earthquake is not so significant, and the stiffness of the building is almost the same as before the earthquake. This result is obtained because of the insignificant increase of the spectrum response parameter in SNI 1726:2019; therefore, the performance level of the building is not affected.